Gratifikasi Sebagai Bentuk Suap Menurut Undang-Undang Nomor 30 Tahun 2001 - Akmal Akmal (Universitas 17 Agustus 1945, 2022)
Efforts to eradicate criminal acts of corruption have become the mandate of the Indonesian nation and have been outlined in the Decree of the Indonesian People's Consultative Assembly (MPR) Number XI/MPR/1998 concerning the Administration of a State that is Clean and Free of Corruption, Collusion and Nepotism. This mandate was then followed up with Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. The application of a reversal of the burden of proof system in reporting gratuities in the context of eradicating corruption has been implemented by Malaysia and Singapore. The implementation of the system of reversing the burden of proof in reporting gratuities in Law Number 20 of 2001 is expected to prevent criminal acts of corruption more optimally and effectively, at least reducing the corrupt practices that have occurred so far.